2011
DOI: 10.1002/jso.22109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postoperative pelvic irradiation after complete resection of metastatic rectal cancer

Abstract: Survival benefit of postoperative RTx in stage IV rectal cancer after complete removal of tumors was not apparent. RTx could be recommended for selected patients at high risk of local recurrence or for palliation of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Although preoperative or postoperative pelvic irradiation has yielded better results in terms of local control for patients with stage II and III rectal cancer [1,2,7], the prognostic roles of these therapies in patients with rectal cancer and metastatic diseases are still unknown. In clinical practice, many oncologists often recommend postoperative chemoradiotherapy for patients with stage IV rectal cancer, in addition to systemic chemotherapy, because pelvic irradiation is believed to possibly strengthen local disease control [3,4,8,9]. However, no definite indications or randomized trials that support this potential role of radiotherapy for this population have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although preoperative or postoperative pelvic irradiation has yielded better results in terms of local control for patients with stage II and III rectal cancer [1,2,7], the prognostic roles of these therapies in patients with rectal cancer and metastatic diseases are still unknown. In clinical practice, many oncologists often recommend postoperative chemoradiotherapy for patients with stage IV rectal cancer, in addition to systemic chemotherapy, because pelvic irradiation is believed to possibly strengthen local disease control [3,4,8,9]. However, no definite indications or randomized trials that support this potential role of radiotherapy for this population have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
“…However, no definite indications or randomized trials that support this potential role of radiotherapy for this population have been reported to date. We previously obtained data suggesting that pelvic irradiation might improve local control in patients with stage IV rectal cancer who underwent curative resection; the rate of locoregional recurrence was twice as high in the 40 patients who did not undergo radiotherapy compared with the 28 patients who did undergo postoperative radiotherapy (22.5 and 7.1%, respectively; p = 0.108) [3]. A recent retrospective study also showed that adjuvant pelvic radiotherapy significantly reduced the pelvic failure rate in rectal cancer with synchronous liver metastasis [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most series include patients who had non-surgical management of synchronous metastasis and differences in timing of radiotherapy (10,(15)(16)(17)(18)(19)(20). The most relevant comparisons to our work involve two studies, which investigated the value of RT in patients undergoing curative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that postoperative pelvic radiotherapy in patients with metastatic rectal cancer does not improve local recurrence and overall outcome [11,12]. The rate of locoregional failure after postoperative radiotherapy in metastatic rectal cancer was 7.1 to 23.1 % compared with 22.5 to 32.6 % of the nonradiation group without significance [12,11].…”
Section: Introductionmentioning
confidence: 95%